2013
DOI: 10.1002/anie.201305475
|View full text |Cite
|
Sign up to set email alerts
|

Study of Intermolecular Interactions in the Corrole Matrix by Solid‐State NMR under 100 kHz MAS and Theoretical Calculations

Abstract: Recent progress in solid-state (SS)NMR spectroscopic methods based on fast magic angle spinning (MAS) [1] has enabled new opportunities for the structural study of small quantities (< 5 mg) of natural abundance samples. Utilizing throughspace and through-bond polarization transfer, indirect detection of low-g nuclei, and suitable homo-and heteronuclear decoupling, one-and two-dimensional (1D and 2D) spectra of such samples can be measured with excellent sensitivity and resolution.[2] However, determination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 33 publications
2
59
0
Order By: Relevance
“…1 H, 13 C, and 15 N backbone and side-chain resonances were assigned using a suite of proton detected 3D spectra correlating backbone and sidechain chemical shifts.…”
Section: Ppm)mentioning
confidence: 99%
See 3 more Smart Citations
“…1 H, 13 C, and 15 N backbone and side-chain resonances were assigned using a suite of proton detected 3D spectra correlating backbone and sidechain chemical shifts.…”
Section: Ppm)mentioning
confidence: 99%
“…High-resolution proton-detected methods were first demonstrated with modest spinning frequencies by today's standards (∼10 kHz) and relied on a reduction of 1 H-1 H couplings by high levels of dilution with deuterium, typically perdeuteration, and complete (8, 9) or partial (10-12) protonation at exchangeable sites. The need for narrow proton resonances without such extreme levels of deuteration has motivated a continuous technological development, resulting in a dramatic increase in the available spinning frequency (13)(14)(15)(16)(17)(18)(19)(20).At MAS frequencies of 40-60 kHz, deuteration and 100% reprotonation at exchangeable sites, primarily amide protons, result in resolved and sensitive spectra, similar in quality to the case of higher dilution levels and lower spinning frequencies (21-23). This opens the way to rapid sequential assignment of backbone resonances (24-27), as well as to the unambiguous measurement of detailed structural and dynamical parameters (28-32).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the suppression of 1 H− 1 H dipolar couplings, ultrafast-MAS dramatically enhances spectral resolution of protons. [45][46][47][48][49] Because of this reason and due to the enhanced signal-to-noise ratio rendered by proton detection, the development of protonbased solid-state NMR techniques has been the main focus of recent ultrafast-MAS studies. [50][51][52][53][54][55][56][57][58][59][60] Recent studies from our laboratory have demonstrated the feasibility of recoupling proton-proton dipolar couplings, 14,[61][62][63] protonbased multidimensional experiments, [64][65][66][67] spectral-editing techniques, 68,69 and proton-proton distance measurements 69 under ultrafast-MAS conditions, whereas effective use of deuteration has also very recently been shown to be useful in proton-proton distance measurements by Reif et al 70,71 We have also shown the role of dipolar couplings that control the efficiency of refocused-INEPT pulse sequence under ultrafast-MAS.…”
Section: Introductionmentioning
confidence: 99%